Cleavage of Desmosomal Cadherins Promotes γ-Catenin Degradation and Benefits Wnt Signaling in Coxsackievirus B3-Induced Destruction of Cardiomyocytes - Zhao, Guangze; Zhang, Huifang M.; Qiu, Ye; Ye, Xin; Yang, Decheng (Frontiers in Microbiology, 2020)
Coxsackievirus B3 (CVB3) is the primary etiologic agent of viral myocarditis, a major heart disease that occurs predominantly in children and young adolescents. In the heart, intercalated discs (ICD) are important structural formations that connect adjacent cardiomyocytes to maintain cardiac architecture and mediate signal communication. Deficiency in ICD components, such as desmosome proteins, leads to heart dysfunction. γ-catenin, a component protein of desmosomes, normally binds directly to desmocollin-2 and desmoglein-2. In this study, we found that CVB3 infection downregulated γ-catenin at the protein level but not the mRNA level in mouse HL-1 cardiomyocytes. We further found that this reduction of γ-catenin protein is a result of ubiquitin proteasome-mediated degradation, since the addition of proteasome inhibitor MG132 inhibited γ-catenin downregulation. In addition, we found that desmocollin-2 and desmoglein-2 were cleaved by both viral protease 3C and virus-activated cellular caspase, respectively. These cleavages led to the release of bound γ-catenin from the desmosome into the cytosol, resulting in rapid degradation of γ-catenin. Since γ-catenin shares high sequence homology with β-catenin in binding the TCF/LEF transcription factor, we further studied the effect of γ-catenin degradation on Wnt/β-catenin signaling. Luciferase assay showed that γ-catenin expression inhibited Wnt/β-catenin signaling. This finding was substantiated by qPCR to show that overexpression of γ-catenin downregulated transcription of Wnt signal target genes, c-myc and MMP9, while silencing γ-catenin upregulated these target genes. Finally, we demonstrated that γ-catenin expression inhibited CVB3 replication. In search for the underlying mechanism, we found that silencing γ-catenin caused down-regulation of interferon-β and its stimulated antiviral genes MDA5, MAVS and ISG15. Taken together, our results indicate, for the first time, that CVB3 infection causes cardiomyocyte death through, at least in part, direct damage to the desmosome structure and reduction of γ-catenin protein, which in return promotes Wnt/β-catenin signaling and downregulates interferon-β stimulated immune responses.